Monitoring the water quality of Belawan Sea for rearing asian seabass Lates calcarifer in a floating net cage system - Vina Iman Sari Lubis; Kukuh Nirmala; Eddy Supriyono; Yuni Puji Hastuti (Jurnal Akuakultur Indonesia)
Belawan is a coastal area located in Medan Belawan District, North Sumatra Province. The aim of the research is to determine the feasibility status of the study location if it is developed as a location for floating net cages (KJA). The research was carried out in the sea waters of Belawan in August–September 2022. The research parameters observed during the research were hydrooceanographic data and water quality data including physical parameters, chemical parameters, biological parameters. Determination of water quality status using the STORET Index, CCME WQI Index and principal component analysis (PCA). Observation parameters during the research were clinical symptoms, histological observations and growth performance of Asian sea bass. The research results show that tides, COD and turbidity are parameters that do not comply with water quality standards. The types of phytoplankton consist of 15 species and 4 classes, namely Cyanophyceae, Chlorophyceae, Bacyllariophyceae and Dynophyceae. Observation total vibrio count (TVC) shows that in all water samples it is Log 105 CFU/mL and in snapper organs (gills, liver, kidneys) there are Log 104-105 CFU/g. The results of the research can be concluded that for each zone in Belawan waters there is no difference in the level of pollution between zones in terms of the STORET index (moderately polluted) and the CCME WQI index (marginal) with limiting factors namely COD and turbidity. Belawan waters are in less than suitable condition in August–September for snapper cultivation activities in floating net cages (KJA) characterized by low SR and ADG values.